Antibiotic Resistance Profiles of Salmonella Isolated from Al-Gharraf River and Iraqi Sewage - Naqaa K. Ali; Heba Qasim Zaghir (Recent Trends in Infectious Diseases, 2024)
Salmonella is a Gram-negative bacterium belonging to the Enterobacteriaceae family. It has a rod-shaped (bacillus) structure. Salmonella is a prominent contributor to gastrointestinal sickness worldwide. In addition, it is the causative agent of more systemic severe disorders such as typhoid and paratyphoid fevers. Salmonella is primarily recognized as pathogens transmitted by water and food to people and animals. Salmonella is often found in water-related epidemics, even though it is routinely detected in surface waters such as recreational waters, irrigation waters, and drinking water sources. The primary specimen for isolating Salmonella is water, which constitutes the principal constituent of the environment. This study aimed to isolate and identify the Salmonella spp. bacteria from water by biochemical tests and antibiotic screening. Ninety-three samples were gathered from the water of the Al-Gharraf river in Nasiriyah city. Out of these samples, 42 (45.16%) tested positive for the presence of Salmonella. Moreover, the occurrence rate of the sewage water is 76.14%, whereas the occurrence rate of river and tap water is 60.11%. Following isolation and identification, Salmonella was subjected to antibiotic susceptibility testing. It was determined that ampicillin exhibited a high level of resistance, while azithromycin displayed a high level of sensitivity.
Keywords: Al-gharraf River; Salmonella spp; antibiotics; river; sewages